Achieving Highly Sensitive Near-Infrared Organic Photodetectors using Asymmetric Non-Fullerene Acceptor - Lee, Un Hak; Park, Byoungwook; Rhee, Seunghyun; Ha, Jong Woon; Whang, Dong Ryeol; Eun, Hyeong Ju; Kim, Jong H.; Shim, Yeongseok; Heo, Junseok; Lee, Changjin; Kim, Bumjoon J.; Yoon, Sung Cheol; et al. (Advanced Optical Materials, 2023)
Organic photodetectors (OPDs) based on non-fullerene acceptors (NFAs) have received considerable attention because of their potential for use in various commercial applications as near-infrared (NIR) light sensing platforms. However, recent OPDs suffer from low NIR photoresponse and large dark/noise currents with narrow bandgap organic photoactive materials. Herein, a π-bridge molecular engineering strategy replacing alkoxythienyl with benzothiadiazole for ultra-narrow bandgap (ultra-NBG) NFAs is designed to achieve simultaneously high photoresponse at NIR region and low noise current density, thereby leading to excellent NIR (≈1050 nm) detectivity (D*). The newly synthesized ultra-NBG NFAs, namely COB and CBT with optical bandgaps below 1.14 eV, present high responsivity (R) with 0.369 and 0.080 A W−1, respectively, at a wavelength of 1050 nm. Especially, with effectively suppressed noise current density, COB-based OPD exhibits a high NIR (≈1050 nm) D* value of 2.18 × 1011 cm Hz1/2 W−1 at −0.5 V bias. The obtained R and D* values for these NFAs exceed or are comparable to those of a commercial Si photodetector at 1050 nm. This work provides important insight into the π-bridge molecular engineering strategy for ultra-NBG NFAs, which facilitate achieving highly sensitive NIR OPDs with high NIR photoresponse and low dark/noise current.
Keywords: Absorbing materials; Asymmetric structures; Intramolecular interactions; Narrow bandgap; Near Infrared; Near-infrared; Near-infrared absorbing material; Non-fullerene acceptor; Organic photodetector; Organics; Ultra narrow bandgap; asymmetric structure; intramolecular interaction; NIR absorbing materials; non-fullerene acceptors; organic photodetectors; ultra narrow bandgap